Median-Average Round Robin (MARR) Algorithm for Optimal CPU Task Scheduling - Purnomo, Rakhmat; Putra, Tri Dharma (Politeknik Ganesha Medan, 2025)
Abstract: In operating systems, multitasking or multiprocessing terms are used. If more than one task operating consecutively, but the users feel that they are running simultaneously, than it is called multitasking. Round robin algorithm is a noted algorithm in multitasking. Several modifications of classical round robin algorithm have been proposed by experts. The idea behind these modifications are to get lower turnaround time and lower waiting time. The main topic’s discussion is about median-average round robin (MARR) algorithm. In this algorithm, the processes are arranged in ascending order. Then we get the median of the burst time. Afterwards, calculation of the average burst time is done. The summation of average and median, divide by two is the time quantum. So, the time quantum will be dynamic, based on each iteration of round robin. First iteration can have different time quantum compared to the second and so on. Each iteration will have one time quantum. Three analysis’s are given. Each with five processes. In the first analysis, time quantum for 1st iteration is 11 and the 2nd iteration is 4. The average turnaround time is 29. The average waiting time is 19. For the second analysis, time quantum for 1st iteration is 10 and the 2nd iteration is 8. The average turnaround time is 24.2. The average waiting time is 13.6. For the third analysis, time quantum for 1st iteration is 10 and the 2nd iteration is 9. The average turnaround time is 23.2. The average waiting time is 12.8.